Stock Price Increase Based on Profitability, Profit and Leverage with Investment Policy as Intervention Variable - Widyakto, Adhi; Octavia, Ayu Nurafni; Fresiliasari, Oktavie (Universitas Semarang, 2025)
This study investigates the impact of Profitability, Revenue, and Leverage, with investment policies as intervention variables, on the share prices of telecommunications subsector companies listed on the Indonesia Stock Exchange from 2019 to 2023. Utilizing a quantitative research approach, this study analyzes secondary data collected from the company's financial statements. The aim of this study was to consider additional performance indicators for a comprehensive understanding of the overall health of the company. The sample consisted of 18 companies selected through purposive sampling, each meeting specific criteria. Statistical analysis was performed using Partial Least Square (PLS) to explore the relationships between the variables under investigation. These findings reveal that ROA, EPS, and DER have a significant positive effect on the Price Income Ratio (PER). In contrast, ROA has a significant negative impact on stock prices, while EPS, DER, and PER have a positive impact on stock prices. In addition, PER mediates the relationship between ROA and DER with stock price but does not mediate the relationship between EPS and stock price